Micropitting And Wear Assessment Of Roller Bearing - Hamidi, Muhammad Nafiz (Universiti Sains Malaysia, 2022)
Rolling element bearing is used in many applications such as in automotive industries, and heavy equipment or machinery. It is important to make sure that the bearing does not fail because it could lead to the failure of the machine. Micropitting is one of the most common phenomena that can be found on the bearing surface that can lead to the failure of the bearing. Micropitting are affected by several factors such as surface topography, material, load, lubricant, temperature, speed, lambda ratio and slide to roll ratio. Lubricant is usually introduced into the rolling contact of the roller bearing in order to control the friction and wear of the bearing which can have an effect on the rate of micropitting formations The purpose of this study is to investigate the micropitting and wear of the roller bearing lubricated with palm oil grease. The experiment is carried out using the roller test rig. The roller surface is scanned using a microscope at a few cycles to observe the progress of the surface micropitting. It is found that the roller surface lubricated with palm grease with a nano additive took the longest time (150000 cycles) for the surface to damage. The wear volume and micropitting depth are the smallest which are 20747 µm3 and -4.4 µmas compared to the other lubricating conditions.